Identification of yeasts isolated from deteriorated strawberry juice of the northwest argentine - Vallejo, Claudia Veronica (2015)
Yeasts can resist extreme conditions better than bacteria, so they play an important role as spoilage of foods and beverages. Procedures used for yeast identification including cellular morphology and fermentation and assimilation tests, sometimes lead to ambiguous results because of phenotypic variability of the strain. Whereby, molecular approaches are consistently used for yeast identification. Tucumán is the leading producer of strawberries in northern of Argentina and strawberry juices are highly consumed in this country; however there are no reports available about the identification of yeasts present in deteriorated Argentinean strawberry juices. The aim of this work was the isolation of yeasts present in deteriorated strawberry juice and their identification in order to find out in the future a possible control compound or solution to this problem. Strawberries with no apparent physical or microbial damage were washed and milled in processor to make 1 liter of juice which was placed in sterile flasks until signs of deterioration appeared. After 10 days of elaboration, strawberry juices showed the first signal of detriment. Samples of deteriorated juices (0.1 ml), were plated onto YMPG agar medium and 1.0 % of chloramphenicol (YMPG-C). YMPG-C plates were aerobically incubated for 48 h at 28°C.Yeast colonies were isolated from streaked YMPG plates. The isolated yeasts were characterized by microscopic and macroscopic morphology; classification in Saccharomyces or non-Saccharomyces yeast; sporulation assay; pseudomycelia formation; growth at different temperature; formation of amylaceous compounds, sugar fermentation, DNA extraction, RFLP, Microsatellite analysis, amplification partial sequencing of ribosomal RNA genes and DNA sequence analysis. Two different colony morphotypes were obtained which were separated into two groups. All isolated yeast were non-Saccharomyces, produced 1-2 ascospores and amylaceous compounds production was not detected. The major differences between both groups were colonies appearance, cellular shaped, growth at 37°C, carbon source fermentation and assimilation. The RFLP analysis of the ITS1/NL-4 amplicons from the strainsVRV-1, VRV-4, VRV-5, VRV-7, VRV-8, VRV-11, VRV-14 y VRV-16 (Group I) showed a similar profile, while the fragments from the strains VRV-2, VRV-3, VRV-6, VRV-9, VRV-10, VRV-12, VRV-13, VRV-15, VRV-17 y VRV-18 (Group II) resulted in a different pattern. The microsatellite amplification patterns obtained with primers (GAC)5 and (GTG)5, allowed us to confirm the division in two groups. The sequence analysis of the rDNA fragment obtained from the isolates of Group I showed a close phylogenetic relationship whith Hanseniaphora osmophila, whereas the same analysis applied to the Group II showed that isolates yeasts are closely related to Starmerella bacillaris. Conclusion: the identification of the isolated yeast could be useful to prevent juice deterioration by controlling these harmful microorganisms.